Aqueous proton batteries based on acetic acid solutions: mechanistic insights. (January 2023) - Gavriel, Bar; Bergman, Gil; Turgeman, Meital; Nimkar, Amey; Elias, Yuval; Levi, Mikhael D.; Sharon, Daniel; Shpigel, Netanel; Aurbach, Doron
Abstract: Large grid energy storage devices are critical for the success of the clean and sustainable energy revolution. As Li-ion batteries are earmarked for electric vehicles and portable devices such as laptops and cellphones, other electrochemical systems should be developed that enable cost-effective, safe, and durable large-scale energy storage. Due to the low cost and non-flammability of aqueous electrolyte solutions, much effort is being put into the development of 'beyond-Li' batteries and super capacitors that can work in these environments. Here, we propose new proton batteries comprising an acetic acid electrolyte solution, Ni II [Fe III (CN)6 ]2/3 ·4H2 O Prussian blue analog cathodes, and Ti3 C2 T x MXene anodes. Both electrodes were investigated independently to discover ideal settings for the electrochemical performance and stability. Significant attention was given to the cathodes' protons storage mechanism. In-situ electrochemical quartz crystal microbalance with dissipation revealed that in acetic acid, hydronium and proton insertion contribute to charge storage, whereas in sulfuric acid-based electrolyte solutions, the main charge carriers are bare protons. 4.5 M acetic acid solution provided the best performance in terms of electrodes' capacitance and rate capability. The battery systems presented here show a promising direction but require further intensive optimization efforts. This research opens the way for research and development of novel proton batteries based on solutions containing common weak acids for more cost-effective and environmentally friendly energy storage systems. Graphical abstract: Image 1 Highlights: Aqueous proton batteries with improved capacity. Acetic acid electrolyte solutions, Prussian blue analog nickel Turnbull's blue cathodes, and MXene anodes. Electrochemical quartz crystal microbalance with dissipation reveals a dual proton insertion mechanism. Hydronium ions into zeolitic sites and Grotthuss type proton conduction.